2017
DOI: 10.14202/vetworld.2017.774-778
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance pattern of Shiga toxigenic Escherichia coli in diarrheic buffalo calves

Abstract: Aim:Aim of the study was to investigate the prevalence, virulence gene profiles, and antimicrobial resistance pattern of Shiga toxigenic Escherichia coli (STEC) in diarrheic buffalo calves from Andhra Pradesh and Telangana States.Materials and Methods:A total of 375 fecal samples from diarrheic buffalo calves of 1-7, 8-30, 31-60, and 61-90 days age were collected from which STEC were isolated, and virulence genes were detected using multiplex polymerase chain reaction. The antimicrobial resistance of isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
13
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
(29 reference statements)
11
13
4
1
Order By: Relevance
“…The high resistances of E. coli isolates to tetracycline in our study were previously supported by many authors (Schroeder et al, 2002;Rigobelo et al, 2006;Alberto et al, 2011 andHang et al, 2019). However, higher resistance to streptomycin, gentamycin, tetracycline, chloramphenicol, sulfamethoxazole/trimethoprim and neomycin in our study was in contrary to other reports by (Wani et al, 2013;Rehman et al, 2014 andSrivani et al, 2017), that reported STEC isolates from diarrheic calves showed high susceptibility to gentamycin and chloramphenicol. The high incidence of resistant or multi-resistant E. coli isolates in the present work may be attributed to that the wide and haphazard using of antimicrobials in animals for treatment, prevention, and control of infectious diseases, and as growth promoters for potential livestock production (Marshall and Levy, 2011).…”
Section: R=resistance I=intermediate S=sensitivesupporting
confidence: 72%
See 2 more Smart Citations
“…The high resistances of E. coli isolates to tetracycline in our study were previously supported by many authors (Schroeder et al, 2002;Rigobelo et al, 2006;Alberto et al, 2011 andHang et al, 2019). However, higher resistance to streptomycin, gentamycin, tetracycline, chloramphenicol, sulfamethoxazole/trimethoprim and neomycin in our study was in contrary to other reports by (Wani et al, 2013;Rehman et al, 2014 andSrivani et al, 2017), that reported STEC isolates from diarrheic calves showed high susceptibility to gentamycin and chloramphenicol. The high incidence of resistant or multi-resistant E. coli isolates in the present work may be attributed to that the wide and haphazard using of antimicrobials in animals for treatment, prevention, and control of infectious diseases, and as growth promoters for potential livestock production (Marshall and Levy, 2011).…”
Section: R=resistance I=intermediate S=sensitivesupporting
confidence: 72%
“…Other studies have supported our result recorded by (Pereira et al, 2011 andShahrani et al, 2014) they showed that all isolates of E. coli exhibited high susceptibility to ciprofloxacin and cefepime and resistance to tetracycline, streptomycin, and sulfamethoxazole-trimethoprim. However, (Srivani et al, 2017) reported high antimicrobial resistance of STEC strains isolated from diarrheic calves to tetracycline (63.21%) and susceptible to chloramphenicol, gentamycin (96.33%) and imipenem (99.06%) in addition to 69.81% of these strains expresses multidrug resistance. Furthermore, (Hang et al, 2019) found that tetracycline was detected as the most resistant antibiotic by E. coli strains followed by sulfamethoxazole, ampicillin, trimethoprim, and ciprofloxacin.…”
Section: Antimicrobial Susceptibility Pattern Of E Coli Serotypes Frmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was aimed at determining the prevalence of STEC and ETEC incriminated in calf diarrhea, with special reference to the Shiga-toxins genes ( stx 1 and stx 2) and enterotoxins genes ( lt and sta ) that govern their pathogenesis, as well as the virulence genes; eae A and f 41, and the screening of their antimicrobial resistance profiles and antimicrobial resistance genes; aad B, sul 1, and bla- TEM. The overall prevalence of E. coli was 28.8%, which is lower than what was reported in diarrheic calves in Egypt (63.6%) [ 13 ], Ethiopia (36.8%) [ 14 ], Argentina (30.1%) [ 15 ] and India (85.04%) [ 16 ]; however, a lower prevalence was reported in other previous studies in Korea (22%) [ 17 ] and Switzerland (5.5%) [ 18 ]. Differences in the prevalence of E. coli may be due to the differences in geography, management practices, floor type, health conditions, and the calf’s age [ 2 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 63%
“…Treatment of different bacterial diseases by antimicrobials in a suboptimal or incomplete dose may develop antimicrobial resistance in animals. Recently in Bangladesh, a report has been published on STEC in buffalo calves with a prevalence of 11.01% (Gupta et al 2018) and another study in India with a prevalence of 35.01% (Srivani et al 2017). Limited number Cite This Article as: Mannan MS, Sabuj AAM, Ray MK, Rabbi F, Bupasha ZB and Sarker MS, 2021.…”
Section: Introductionmentioning
confidence: 99%